1992
DOI: 10.1111/j.1365-2230.1992.tb00249.x
|View full text |Cite
|
Sign up to set email alerts
|

The inter-relation between inflammation and epidermal proliferation in normal skin following epicutaneous application of leukotriene-B4-an immunohistochemical study

Abstract: Topical application of leukotriene-B4 (LTB4) on normal skin has been used as an in-vivo model to investigate cutaneous inflammation and epidermal proliferation, which are important phenomena in the pathogenesis of psoriasis. The aim of the present investigation is to further elucidate the interrelation between inflammation and epidermal proliferation, using specific monoclonal antibodies as markers for the different cell types involved. Aliquots of LTB4 were applied on the upperarms of eight healthy volunteers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Furthermore, the changes in proliferation and differentiation markers found after challenging the skin resemble the findings of previous studies [8,9,19], indicating that this model is highly reproducible and that the execution of the LTB 4 application was done accurately.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Furthermore, the changes in proliferation and differentiation markers found after challenging the skin resemble the findings of previous studies [8,9,19], indicating that this model is highly reproducible and that the execution of the LTB 4 application was done accurately.…”
Section: Discussionsupporting
confidence: 75%
“…During the past decades, the inflammatory response to epicutaneous application of leukotriene B 4 (LTB 4 ) has been studied extensively and can be regarded as an established model to mimic psoriasis-like inflammation of the skin [8,9,10,11,12]. It is known that in psoriatic lesions high levels of LTB 4 are present [13,14] which are produced by activated innate immune cells [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in Lta4h −/− and Ltb4r1 −/− mice demonstrated that LTB 4 and BLT1 are both important for neutrophil accumulation into tape-stripped mouse skin. The role of LTB 4 in neutrophil recruitment to the skin is supported by the observation that epicutaneous application of LTB 4 in normal healthy volunteers results in local neutrophil infiltration (de Jong et al, 1992). LTB 4 induces itch-associated scratching response in mice (Kim et al, 2007).…”
Section: Discussionmentioning
confidence: 63%
“…Prior to the identification of BLT1, it was shown that LTB 4 bound a small proportion of human peripheral blood T cells 11,12 and could induce their chemotaxis both in vitro and in vivo after topical application of LTB 4 . 11,13 Studies have noted very low-level expression of BLT1 in human peripheral blood T cells as measured by RNA levels or cell surface protein expression. 14,15 The phenotype and function of human BLT1 ϩ T cells and the functional significance of the LTB 4 -BLT1 lipid chemoattractant pathway in human adaptive immune cell trafficking, therefore, still remain to be defined.…”
Section: Introductionmentioning
confidence: 99%